Client Readiness Indicators in Counseling Guidance: A Literature Review and Implications for Counseling Practice - Diana Rezu Okti; Mudjiran; Yeni Karneli (Manajia: Journal of Education and Management, 2025)
Client readiness is a key factor influencing success in the guidance and counseling process. This article presents a literature review related to indicators of client readiness that are important in determining the effectiveness of counseling. Various studies have shown that client readiness can be influenced by internal factors, such as personal motivation, self-awareness, and emotional readiness, as well as external factors, such as social support and life situations faced. This article identifies key indicators of client readiness, including openness to change, ability to recognize problems, and commitment to be actively involved in the counseling process. In addition, the implications of these indicators for counseling practice are also discussed, including the importance for counselors to develop appropriate strategies in assessing and facilitating client readiness. By understanding indicators of client readiness, guidance and counseling practitioners can design more effective interventions, which focus on increasing client motivation and involvement. This article is expected to provide useful insights for counselors and researchers to better understand the dynamics of client readiness and its application in more optimal counseling practice.